The Analysis of Different Perceptions between PPAk Students, KAP Auditors and Company Manager toward Public Accountant Responsibility Related to Expectation Gap - Thomas, Gen Norman (Binus Business Review, 2015)
This study is in research domain of behavioral accounting that is based on the current aspect is stillÂ interesting to explore.This study aims to reveal differences in perceptions of students, auditors and companyÂ managers to public accountant responsility related to expectation gap that includes fraud disclosures, maintainÂ of independence, providing early warning of possibility of business failure, violation of law and improving auditÂ quality. This research is quantitative research using descriptive and comparative research method. DataÂ collective tehnique use survey method with sample was determined by non probability under convenience sample.Â Data quality was examined with using cronbachâs alpha shows the data is valid and realible. Data normality testÂ used independent t test showed data in normal curve, no multicolinearity and no hetrogenity. First to fifthÂ hyphotesis showed the difference of perception amongs PPAk students, KAPâs auditors and company managersÂ to public accountant responsibility in various dimensions of expectation gap in Jakarta.